Analisis Perubahan Kualitas Udara dengan Memanfaatkan Remote Sensing di Kawasan PLTU Teluk Sirih Kecamatan Bungus Teluk Kabung Kota Padang - Yulianita Yulianita; Novelisa Suryani; Heny Mariati (Jurnal Pembangunan Nagari, 2022)
One of the impacts of PLTU development is air pollution. The study aims to analyze the average and identify changes in air quality in 2013 (before the power plant operates) and 2020 (after the power plant operates) in Bungus Teluk Kabung District by descriptive quantitative.analysis. Changes in air quality were analyzed by Landsat 8 satellite images in 2013 and 2020 with parameters were PM10, SO2 and NOx.The average value of the parameter is calculated based on the air quality algorithm, and to measure changes in air quality standards apply ISPU. The results showed an average improvement in all air quality parameters. Based on the ISPU distribution of PM10 values increased by 1 μg/m³, in 2013 the average value (1.9 μg/m³), in 2020 it became (2.9 μg/m³), included in the good category. SO2 values in the medium category with an increase of 0.7 ρρm, in 2013 (63.3 ρρm) and in 2020 (64 ρρm). NOx is in the unhealthy category with an increase of 0.1 μg/m³, in 2013 (173.5 μg/m³) and in 2020 (173.6 μg/m³). The results of the wilcoxon difference test showed that all air quality parameters had a significant value of < 0.05, meaning that there was a significant difference in air quality before and after the power plant was built. The PLTU is expected to immediately minimize the smoke produced by burning coal using Clean Coal Technology.